Experimental Study on Long-Term Ring Deflection of Glass Fiber-Reinforced Polymer Mortar Pipe - Sun-Hee Kim; Soon-Jong Yoon; Wonchang Choi (Advances in Materials Science and Engineering)
Long-term pressurizing of buried glass fiber-reinforced polymer (GFRP) pipe will result in the reduction of stiffness in the pipes. It leads to excessive deflections in long-term design limits. In situ tests were performed for 664 days to measure deflections of buried GFRP pipe with a large diameter of 2,400 mm. Based on the field test results, finite element analysis was conducted to determine the pipe deflections with respect to the soil conditions and buried depth as variables. Regression analysis has been conducted to determine the long-term deflection of the GFRP pipe after 50 years of construction. The long-term deflection of the GFRP pipe was less than 5 percent suggested by the existing specifications including ASTM D5365 and AWWA M45. The comparison indicates the current specifications significantly conservative to predict long-term deflection of the buried GFRP pipe.